Crucible of Fire : Nineteenth-Century Urban Fires and the Making of the Modern Fire Service - Hensler, Bruce, 1953- (Book collections on Project MUSE., 2011)
How the tragedies of the nineteenth-century's great municipal fires changed firefighting today.